Ecologia comportamental reprodutiva de Diastatops obscura Fabricius (Insecta, Odonata) - Irusta, Jorge Bañuelos (2007)
In this thesis I discuss the reproductive behaviour and ecology of the libellulid Diastatops obscura Fabricius, 1775, (Insecta: Odonata) in natural conditions. Populations of this species were studied on the middle stretch of the Pitimbu River, Parnamirim municipality, Rio Grande do Norte, Brazil, during four discontinuous periods between 2002 and 2004. The objectives include the description of strategies and behaviors of both sexes, with especial interest in the intra-male competition for territories and females, the mate selection by females and the importance of male body size and other secondary characters on their reproductive success; from an adaptationist point of view. It was observed that the behavior of males and females in the reproductive areas are interrelated : the males came earlier to compete for the best territories and the females waited the result of that competition to be fertilized by dominants males, which preferably occupied areas near the river margin. The reproductive success of males with territories on the margin, estimated by number of copulations, ovipositions and days acting as territorial, was better than obtained by more separated territorial males and by satellite males. The body size of males is an important factor for the copulation and oviposition taxes and for the number of territorial days, favoring the biggest individuals. I also discuss the apparently importance of wing brilliance and wing integrity on male reproductive success. On inter-sexual relationships, I proved that females of D. obscura participate in mate selection, rejecting non-territorial males or substituting their sperm for other of higher status